2000
DOI: 10.1152/jappl.2000.89.6.2407
|View full text |Cite
|
Sign up to set email alerts
|

Ventilation-perfusion matching in long-term microgravity

Abstract: We studied the ventilation-perfusion matching pattern in normal gravity (1 G) and short- and long-duration microgravity (microG) using the cardiogenic oscillations in the sulfur hexaflouride (SF(6)) and CO(2) concentration signals during the phase III portion of vital capacity single-breath washout experiments. The signal power of the cardiogenic concentration variations was assessed by spectral analysis, and the phase angle between the oscillations of the two simultaneously expired gases was obtained through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…The iV/Q slope seen over the first half of phase III [the most sensitive indicator of V A/Q inhomogeneity from this test (37)] was slightly elevated in G compared with standing in 1G, lending credence to previous speculation (33) that gravity in fact provides a degree of matching between ventilation and perfusion in the normal upright human lung. The result is also consistent with a previous study in two subjects aboard Mir for ϳ6 mo, which showed that the matching of ventilation to perfusion was unaltered by the time spent in G (44).…”
Section: Pulmonary Gas Exchangesupporting
confidence: 93%
See 1 more Smart Citation
“…The iV/Q slope seen over the first half of phase III [the most sensitive indicator of V A/Q inhomogeneity from this test (37)] was slightly elevated in G compared with standing in 1G, lending credence to previous speculation (33) that gravity in fact provides a degree of matching between ventilation and perfusion in the normal upright human lung. The result is also consistent with a previous study in two subjects aboard Mir for ϳ6 mo, which showed that the matching of ventilation to perfusion was unaltered by the time spent in G (44).…”
Section: Pulmonary Gas Exchangesupporting
confidence: 93%
“…There were only small changes in O 2 uptake (V O 2 ), CO 2 output (V CO 2 ), and end-tidal PO 2 and PCO 2 . The matching of ventilation to perfusion has been reported to remain unaltered in long-duration G (44). However, long-duration bed rest of 113 days showed a reduction VC and diffusing capacity of the lung for CO immediately after bed rest that appeared to persist for up to 2 wk into the recovery period (29).…”
mentioning
confidence: 99%
“…The distribution of ventilation and pulmonary blood flow (V A /Q ) is also altered in microgravity. V A /Q matching becomes more homogenous in microgravity but seems to return to baseline with return to 1g (86).…”
Section: Potential Mechanismsmentioning
confidence: 92%
“…Several studies have shown differences between lung function under different gravity conditions, especially regarding perfusion 61–63 . As represented in Figure 4, pulmonary perfusion is believed to be more homogeneous in microgravity, although a residual inhomogeneity is still detected 64–66 . This more even distribution of capillary blood flow leads to a more efficient interface between the gas and the blood in the lungs.…”
Section: Physiological Changes During Space Flightmentioning
confidence: 96%
“…[61][62][63] As represented in Figure 4, pulmonary perfusion is believed to be more homogeneous in microgravity, although a residual inhomogeneity is still detected. [64][65][66] This more even distribution of capillary blood flow leads to a more efficient interface between the gas and the blood in the lungs. This may explain the improved membrane diffusion capacity observed in microgravity compared to both upright and supine preflight controls.…”
Section: Organ Perfusionmentioning
confidence: 99%